Conservation of a DNA Replication Motif among Phylogenetically Distant Budding Yeast Species. (16th June 2021) - Maria, Haniam; Kapoor, Shivali; Liu, Tao; Rusche, Laura N
Abstract: Eukaryotic DNA replication begins at genomic loci termed origins, which are bound by the origin recognition complex (ORC). Although ORC is conserved across species, the sequence composition of origins is more varied. In the budding yeast Saccharomyces cerevisiae, the ORC-binding motif consists of an A/T-rich 17 bp "extended ACS" sequence adjacent to a B1 element composed of two 3-bp motifs. Similar sequences occur at origins in closely related species, but it is not clear when this type of replication origin arose and whether it predated a whole-genome duplication that occurred around 100 Ma in the budding yeast lineage. To address these questions, we identified the ORC-binding sequences in the nonduplicated species Torulaspora delbrueckii . We used chromatin immunoprecipitation followed by sequencing and identified 190 ORC-binding sites distributed across the eight T. delbrueckii chromosomes. Using these sites, we identified an ORC-binding motif that is nearly identical to the known motif in S. cerevisiae . We also found that the T. delbrueckii ORC-binding sites function as origins in T. delbrueckii when cloned onto a plasmid and that the motif is required for plasmid replication. Finally, we compared an S. cerevisiae origin with two T. delbrueckii ORC-binding sites and found that they conferred similar stabilities to a plasmid. These results reveal that the ORC-binding motif arose prior to the whole-genome duplication and has been maintained for over 100 Myr.